(untitled) (Research, Society and Development, 2022)
The aim of this study was to evaluate, through a review, the interrelationship between COVID-19, periodontitis and some oral pathologies. The transmission of COVID-19 occurs through small droplets in the nose or mouth containing a viral particle that is expelled by people during coughing, speaking, or sneezing, for example. About 20% of those infected from inpatient and 5% will likely occur from a bed in intensive care. People with underlying medical conditions are more likely to develop serious illness. Patients with preexisting comorbidities such as diabetes, hypertension, cardiovascular diseases, among others, may be more susceptible to developing the most severe form of COVID-19. Several systemic changes may be associated with this pathology, such as disorders in the oral microbiota, an increase in the number of microorganisms present in it, which would lead to a greater propensity for oral pathologies. Virus entry can subvert the host’s immune system and oral microbiota, triggering dysbiosis that allows for superinfection, understanding the association of periodontal disease with severe COVID-19. The present study aims to assess an association between pathology oral and the worsening of COVID-19, as well as to identify its relationship between preexisting symptoms and oral pathologies.